2016
DOI: 10.1515/pjvs-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium and Aspergillus mycotoxins effects on dairy cow health, performance and the efficacy of Anti-Mycotoxin Additive

Abstract: One hundred two samples of feeds made in Lithuania, which included maize silage, grass-legume silage, hay and ensiled crimped maize were investigated during 2008-2012 for contamination with some mycotoxins. The highest concentrations of mycotoxins determined were those of deoxynivalenol (DON) -471.0 μg/kg and aflatoxin B 1 (AFB 1 ) -21.2 μg/kg in ryegrass silage from bales, and zearalenone (ZEA) -625.0 μg/kg in maize silage from trenches. The present study has been carried out based on these data because anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
6
20
2
8
Order By: Relevance
“…Various parts of the nephron are prone to aflatoxins particularly the AFB1 and its metabolites directed towards nephrotoxicity before it is discharged in the animal urine (Sharma et al, 2011). Serum biochemical parameters increased by aflatoxin treatment were ALT, AST, ALP, total bilirubin, BUN and creatinine (Jovaisiene et al, 2016;Abbès et al, 2010) which is in accordance with our study. Decrease in protein content because of aflatoxin has been described because of inclined necrosis of the kidney [Sharma et al, (2011); Mohammed and Metwally (2009); Wangikar et al,(2005); Lakkawar et al, (2004)] which is agreed by our study in which increased level of BUN and creatinine as well due to lethal effects of AFB 1 on the kidneys.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Various parts of the nephron are prone to aflatoxins particularly the AFB1 and its metabolites directed towards nephrotoxicity before it is discharged in the animal urine (Sharma et al, 2011). Serum biochemical parameters increased by aflatoxin treatment were ALT, AST, ALP, total bilirubin, BUN and creatinine (Jovaisiene et al, 2016;Abbès et al, 2010) which is in accordance with our study. Decrease in protein content because of aflatoxin has been described because of inclined necrosis of the kidney [Sharma et al, (2011); Mohammed and Metwally (2009); Wangikar et al,(2005); Lakkawar et al, (2004)] which is agreed by our study in which increased level of BUN and creatinine as well due to lethal effects of AFB 1 on the kidneys.…”
Section: Resultssupporting
confidence: 93%
“…Short term, high dosage exposure, especially to Aflatoxin B 1 (AFB 1 ), the most strong of these toxins, might cause acute aflatoxicosis. Jovaisiene et al (2016); Gowda et al (2009); Samuel et al (2009) and Tripathi et al (2008) observed that aflatoxin might cause hemorrhagic liver necrosis, steatosis, bile duct proliferation and subsequent organ failure, also higher levels of ALT and AST resulted in hepatocyte degeneration and leakage of enzymes, agreed with our study. Aflatoxins have been caused liver cirrhosis as well as liver cancers (Thrasher, 2012;Wu and Khlangwiset, 2010); Wu and Tritscher, 2011).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, Winkler et al [ 17 ] found that cows fed a diet containing 0.5 mg/kg ZEA and 5 mg/kg deoxynivalenol (DON) did not suffer significant effects on their performance. However, in an experimental study of dairy cows to which a diet contaminated with 1 mg/kg ZEA, 600 μg/kg DON, and 10 μg/kg AFB1 was fed, negative effects on somatic cell count, blood parameters, and immunity were identified [ 18 ]. Therefore, we investigated the toxic effects of mixtures of AFB1, OTA, and ZEA on milk yield, dry matter intake (DMI), blood metabolic markers, immune function, and antioxidant status in lactating dairy goats.…”
Section: Introductionmentioning
confidence: 99%
“…For example, soybeans are generally considered resistant to Aspergilli colonization and a atoxins contamination (Njobeh et al, 2009;Gupta & Venkitasubramanian, 1975) whereas zearalenone is commonly detected in corn, wheat and corn-based feeds (Driehuis et al, 1992;Schmidts et al, 2014;Lee and Ryu, 2017). Nevertheless, considering that a atoxins and zearalenone exert synergistic effects on livestock including cattle (Jovaišienė et al, 2016;Huang et al, 2018), the high incidences of these mycotoxins in major concentrate feedstuffs for dairy animals like CB is cause for concern among small scale dairy farmers in Malawi.…”
Section: Discussionmentioning
confidence: 99%